Correction: Anion-driven tetrel bond-induced engineering of lead(ii) architectures with N′-(1-(2-pyridyl)ethylidene)nicotinohydrazide: experimental and theoretical findings. Issue 12 (24th May 2022) - Mahmoudi, Ghodrat; Safin, Damir A.; Mitoraj, Mariusz P.; Amini, Mojtaba; Kubicki, Maciej; Doert, Thomas; Locherer, Franziska; Fleck, Michel
Abstract : Correction for 'Anion-driven tetrel bond-induced engineering of lead(ii ) architectures with N ′-(1-(2-pyridyl)ethylidene)nicotinohydrazide: experimental and theoretical findings' by Ghodrat Mahmoudi et al., Inorg. Chem. Front., 2017, 4, 171–182, ; https://doi.org/10.1039/C6QI00477F